A systematic review with meta‐analysis on functional changes associated with neck pain in adolescents. (10th January 2019) - Andias, Rosa; Silva, Anabela G.
Abstract: Background: Neck pain (NP) is highly prevalent in young people, but there has been no systematic review synthetizing the functional changes associated with this in adolescents. The aim of the present study was to identify and assess critically the evidence on the functional changes associated with NP in adolescents, specifically for: (a) posture; (b) postural control; (c) range of motion; (d) proprioception; (e) muscle function; and (f) sensory threshold. Methods: We searched PubMed, ScienceDirect, Web of Science, PEdro, Scielo, Scopus and Academic Search Premier databases for relevant studies. Two reviewers screened studies for inclusion and assessed the quality of the included studies. One reviewer extracted relevant data from the included studies. A meta‐analysis was performed for studies that measured forward head posture (FHP). Results: Ten studies were included and a total of 15 comparisons for different variables were made. When compared with adolescents without NP, those with NP showed no differences in cervicothoracic posture or FHP. However, statistically significant differences were found for range of motion: weighted mean difference (WMD) from –14.0° (–21.1° to –1.1°) to 9.4° (2.8° to 16.0°); flexor muscle endurance: WMD –11.4 (–21.8 to –0.9) s; extensor muscle endurance: WMD –42.0 (–77.8 to –6.3) s; joint repositioning error for right and left rotation: WMD 1.9° (0.8° to 2.9°) and 2.4° (1.3° to 3.5°), respectively; and pressure pain threshold: WMD from –15.6 (–18.5 to –12.8) to –9.3 (–11.3 to 7.2) N/ cm². Conclusion: There is very limited to limited evidence that there is no difference in posture between adolescents with and without NP, and that there is a difference for range of motion, muscle function, proprioception and pressure pain threshold.